Anteseden dan Konsekuensi Implementasi Sistem Akrual Basis (Studi Empiris Pada Satuan Kerja Perangkat Daerah Provinsi Lampung) - Lego Waspodo; Dona Primasari; Indayani Indayani (Jurnal Telaah dan Riset Akuntansi, 2017)
This study examined the antecedent variables of  implementation  accrual basis system and its consequences.  The  antecedent variables are : adaptation  and the manager support.  The Concequences are  satisfaction and  performances of the officer . This research represented the empirical test which was usingconvienence sampling  technics in data collection.  Data were collected from 107 officers of the local government  in Lampung province.  Data analysis used was Structural Equation Model (SEM) with using program AMOS 20.0. Result of hypothesis examination  indicated that four  hypothesis raised are accepted.KEYWORDS : Adaptation officer, manager support, implementation accrual basis system, satisfaction and performance officer.